New corn resistant lines to stalk rot disease (Dickeya zeae) in Indonesia - SURIANI SURIANI; BAHARUDDIN PATANDJENGI; AMRAN MUIS; MUHAMMAD JUNAID; HISHAR MIRSAM; MUHAMMAD AZRAI; ROY EFENDI; AMELIA SEBAYANG (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Suriani, Patandjengi B, Muis A, Junaid M, Mirsam H, Azrai M, Efendi R, Sebayang A. 2023. New corn resistant lines to stalk rot disease (Dickeya zeae) in Indonesia. Biodiveritas 24: 3190-3200. Stalk rot disease caused by Dickeya zeae is one of the important diseases of corn in Indonesia. Host resistance cultivars are an effective and sustainable control measure of the disease. Therefore, the present study aimed to evaluate the resistance of 15 S1 hybrid maize lines to stalk rot disease. The research was conducted in two seasons (DS and WS) using a randomized block design with 3 replications. The D. zeae suspension with 108cfu/mL concentration was inoculated into the plant test 45 Days After Planting (DAP). Disease incidence and severity were observed during the two seasons. The results showed that all tested lines were infected with stalk rot disease but had various resistance reactions. Disease incidence and severity in the dry season were higher than in the rainy season. In the rainy season all test lines followed the 3 models of disease development, but in the dry season, all lines followed the monomolecular model. Further analysis showed that 3 lines of hybrid maize had the lowest AUDPC value with a protection index of more than 50% in two growing seasons. Stalk lignin content had negative correlation with a disease incidence of -0.60877, so it can be used as a parameter of plant resistance to disease. Tested lines that show resistance to the disease could potentially be useful as new varieties of maize.